Reliable and Efficient Way to Broadcast Messages in a Group by Trust-Based Broadcast (TBB) Scheme - Aikebaier, Ailixier; Enokido, Tomoya; Takizawa, Makoto (Computing and Informatics, 2012)
Nowadays information systems are being shifted to distributed architectures, i.e. Grid and Peer-to-peer (P2P) models to obtain the benefits like scalability, autonomy, and fault-tolerance. We consider the P2P model as a fully distributed, scalable system, which is composed of peer processes (peers). Here, a group of multiple peers cooperate with each other. Peers have to efficiently and flexibly deliver messages to every peer of the group in P2P overlay networks. In order to efficiently and reliably broadcast messages in a scalable group, we take advantage of the multipoint relaying (MPR) mechanism. Here, each peer sends messages to only a subset of its acquaintances. However, if a peer which forwards messages to other peers is faulty, the peers cannot receive messages. In this paper, we newly discuss a trustworthiness-based broadcast (TBB) algorithm where only trustworthy peers forward messages. That is, untrustworthy peers are peers which cannot forward the messages due to some faults. Here, the transmission fault implied by faults of untrustworthy peers can be reduced. We evaluate the TBB algorithm in terms of the number of messages transmitted.